The Impact of the Unity of Form and Content in the Visual Arts on Human Spirituality - Zhabborov Erkin Hollievich (Genius Journals, 2022)
Organizing the construction of the car plant in the flow method of calendar plan modeling, creating a methodology for developing a calendar plan, identifying technical and economic advantages and applying them in design practice.
Keywords: Art; Fine Art; Realism; Composition